Pengaruh Citra Merek dan Kualitas Layanan Terhadap Kepuasan Pelanggan Kargo dan Dampaknya atas Loyalitas Pelanggan Pada PT Citilink Indonesia - Octoriviano, Fajar Adhitia; Simarmata, Juliater; Pahala, Yosi; Setiawan, Agus; Saribanon, Euis (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
Effort to maintain and increase customer loyalty, companies must pay attention to the brand image that is built, ensure consistent, and focus on overall customer satisfaction. Thus, the company can obtain long-term benefits from loyal customers and has the potential for sustainable business growth in the cargo industry. This study aims to analyze whether there is an influence of brand image, service quality, and customer satisfaction on customer loyalty on Citilink Indonesia Cargo customers using a quantitative method, with research samples taken based on the Slovin formula. This research provides important insights for cargo companies in developing effective marketing strategies. Uses technical analysis of the Structural Equation Model (SEM). The results of the study concluded that there was no direct effect of brand image on customer loyalty. There is a direct effect of service quality on customer satisfaction. There is a direct effect of brand image on customer loyalty. There is no direct effect of customer satisfaction on customer loyalty. There is no evidence that brand image indirectly affects customer loyalty through customer satisfaction. There is an influence of service quality indirectly affecting customer loyalty through customer satisfaction.